2012
DOI: 10.1002/art.34625
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of skeletal muscle weakness in a mouse model of inflammatory myopathy

Abstract: OBJECTIVE It is generally believed that muscle weakness in patients with polymyositis and dermatomyositis is due to autoimmune and inflammatory processes. However, it has been observed that there is a poor correlation between the suppression of inflammation and a recovery of muscle function in patients. We have therefore hypothesized that non-immune mechanisms also contribute to muscle weakness. In particular, it has been suggested that an acquired deficiency of AMP deaminase (AMPD1) may be responsible for mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 62 publications
2
50
0
Order By: Relevance
“…Here, I also observed similar trends in the force of hind-limb grip force, with lama4 weakened grip force suggests a non-progressive defect, which is in agreement with the coordination and body balance studies previously conducted by (Patton et al, 2001). Weaker grip force could result from alterations in fibre type compositions involving increased proportion of slow fibre types (Type I) with downregulation of fast fibre types (Coley et al, 2012;Lamboley et al, 2015). In order to determine this, I looked at fibre type expression in gastrocnemius muscles at 3MO and aged mice.…”
Section: Weaker Grip Force In Lama4supporting
confidence: 91%
“…Here, I also observed similar trends in the force of hind-limb grip force, with lama4 weakened grip force suggests a non-progressive defect, which is in agreement with the coordination and body balance studies previously conducted by (Patton et al, 2001). Weaker grip force could result from alterations in fibre type compositions involving increased proportion of slow fibre types (Type I) with downregulation of fast fibre types (Coley et al, 2012;Lamboley et al, 2015). In order to determine this, I looked at fibre type expression in gastrocnemius muscles at 3MO and aged mice.…”
Section: Weaker Grip Force In Lama4supporting
confidence: 91%
“…This uncoupling of the ETC would result in a reduced ATP synthesis rate, creating an energy deficit, which again may contribute to muscle dysfunction [36]. Such a hypothesis is supported by recent in-vivo studies in the H2-k b murine model of myositis that has shown metabolic disturbances, whereby a deficiency in the enzyme AMP deaminase 1 (AMPD1) depresses muscle Adenosine diphosphate (ADP) and AMP levels, thus, causing muscle weakness derived from a bioenergetic imbalance [9]. Moreover, mitochondrial abnormalities have been described in IBM, which correlated with severity of disease [37 & ].…”
Section: The Endoplasmic Reticulum-reactive Oxygen Species Linkmentioning
confidence: 89%
“…Specifically, many patients with apparently treatment-responsive disease, that is, little or no radiographic evidence for myoedema or histological evidence for T-cell infiltrations, remain weak and sometimes profoundly so, even without evidence of muscle damage [8]. Moreover, it has been shown that weakness may precede inflammatory cell infiltrations, for example, in an established murine model of IIM [9]. It thus appears that nonimmune cell-mediated mechanisms may play an important role in the induction of muscle weakness in IIM [10,11].…”
Section: Introductionmentioning
confidence: 98%
“…AMPD1 is exclusively expressed in skeletal muscle, whereas AMPD2 and AMPD3 are ubiquitously expressed. Deficiencies in all three AMPDs have been reported in humans (7), and mutations in AMPD1 were associated with muscle weakness or pain in certain patients (10,11). AMPD2 deficiency is associated with pontocerebellar hypoplasia, which is a rare inherited and progressive neurodegenerative disorder (12).…”
Section: Introductionmentioning
confidence: 99%